How does equity financing impact non-performing financing? Evidence from Indonesia - Melati, Sophis Listy; Risfandy, Tastaftiyan; Pratiwi, Desti Indah; Hartomo, Deny Dwi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2024)
This study aims to investigate the impact of equity financing on non-performing financing (NPF) in Islamic commercial banks in Indonesia. To address this issue, we conducted a panel data regression analysis on 12 Islamic commercial banks in Indonesia from 2010 to 2022. The finding of this study suggests that an increase in equity financing is associated with a lower NPF ratio of Islamic banks. While it is theoretically argued that Islamic banks’ equity financing may be associated with higher risk, our empirical evidence indicates the opposite, suggesting an improved risk profile. Indonesia presents a favorable environment for the application of equity financing for Islamic banks because large Islamic banks in Indonesia are often government-owned, which can lead to“safe” loan portfolios and strong loan repayment. Indonesia is also considered a religious country, creating a suitable environment for mudarabah and musharakah financing. Our findings suggest that Islamic banks in Indonesia should consider offering more equity financing, particularly for low-risk projects, such as those initiated by the governments.